FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN INFORMASI AKUNTANSI PADA USAHA MIKRO KECIL MENENGAH (Survei Pada UMKM Di Kecamatan Aikmel Lombok Timur) - Yuliati, Ni Nyoman; Khotmi, Herawati (Jurnal Aplikasi Akuntansi, 2017)
This study aims to examine the effect of education level, business size, length of business, and the lead time of the company towards the use of accounting information on UMKM in Aikmel Sub-district of East Lombok. Therefore, this research variable consists of 4 (four) independent variables, namely education level (X1), business size (X2), business length (X3), and lead time of company (X4) and its dependent variable is the use of accounting information (Y). The population in this study is all UMKM located in District Aikmel East Lombok recorded in the Department of Cooperatives and UKM East Lombok regency. The sample was taken using simple random sampling that is random sampling. The data were obtained by spreading 55 questionnaires to 55 respondents in Aikmel sub-district of East Lombok which then given to the owner, manager or staff who have the highest rank on the UMKM which is sampled. The data were analyzed using multiple linear regression which was processed using SPSS softwere to know the influence of factors together or one by one against the use of accounting information. The results of this study indicate that the variable level of education, size of business, length of business, and lead time of the company have a significant effect on the use of accounting information partially or simultaneously.